Maize pre‑breeding for resistance to corn stunt - Teixeira, Flavia França; Costa, Flaviane Malaquias; Sábato, Elizabeth de Oliveira; Leite, Carlos Eduardo Prado; Meirelles, Walter Fernandes; Guimarães, Claudia Teixeira; Belicuas, Silvia Neto Jardim (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to select maize families derived from backcrossing between the composite NAP Corn Stunt (donor parent) and inbreed lines (recurrent parents), as to grain yield and resistance to corn stunt, and to evaluate the efficiency of the use of molecular markers in the phenotypic evaluation for the selection of genotypes with high grain yield. One hundred genotypes were evaluated in five environmental conditions in the 2009/2010 crop season. We selected RC1F2 families, which combine high grain yield present in the recurrent parents to resistance to corn stunt present in the donor parent. The selected maize families for agronomic performance and resistance to corn stunt were: L228‑3‑324‑S, L228‑3‑237‑R, L228‑3‑109‑R, which were indicated for crosses with lines of the flint heterotic group; and L3‑422‑R and L3‑586‑R, which were indicated for crosses with lines of the dent heterotic group. For selecting genotypes with high grain yield, the molecular marker‑assisted selection is not efficient for the recovery of the recurrent parent genotype, when compared to the phenotypic evaluation.